A Systematic Review of Sustainable Higher Education Assessment Systems: Indicators, Models, and Future Directions - Mesra, Trisna; Kamil, Insannul; Hadiguna, Rika Ampuh (FKIP Universitas Lampung, 2025)
A Systematic Review of Sustainable Higher Education Assessment System: Indicators, Models, and Future Directions. Objective: Evaluation of the sustainability of higher education institutions (HEIs) has become a major focus in academia, especially as evaluation and ranking systems have evolved into increasingly complex ones. This study aims to provide a set of simple indicators for national policy makers to facilitate the measurement of progress towards sustainability in the higher education sector. Methods: Using a qualitative descriptive approach and a Systematic Literature Review (SLR) method, this study examines 16 types of higher education ranking systems and 16 previous research findings based on the UNEP sustainable higher education framework policy, in order to develop a set of indicators specific to the sustainable higher education sector. Articles were selected using the keywords